Monitoring international funding for the fight against climate change: A system yet to be built - Serge Tomasi (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The fight against climate change is an emblematic public good that has been at the top of the international agenda for many years. Since 1992, the United Nations Conferences of the Parties (COPs) have laid down principles to guide international action and have approved commitments, particularly of a financial nature. These principles include the additionality of climate finance to official development assistance (ODA), the common but differentiated responsibilities of the States party to the Convention, and the "polluter pays" rule. A key element in getting developing countries to sign up to the climate agreements, particularly low-income countries (LICs) and small island developing states (SIDS), has been the commitment to annual financial transfers from industrialised countries to developing countries (DCs) to offset the additional costs incurred by the ecological transition.
Keywords: 330; Climate change; Development financing; Climate